Global, regional and national burden of diabetes mellitus type 2 attributable to low physical activity from 1990 to 2021 and projections to 2050: a finding from the global burden of disease study 2021 - Zhang, Ning; Qu, Xuan; Kang, Lin (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundThis study aims to assess the global burden of type 2 diabetes mellitus (T2DM) attributable to low physical activity from 1990 to 2021 and forecast of its global burden by 2050 using GBD 2021 data.MethodThis study uses data from the GBD 2021 to examine the global burden of T2DM attributable to low physical activity, focusing on deaths, disability-adjusted life years (DALYs), years lived with disability (YLDs), and Years of Life Lost (YLLs). Descriptive analysis was performed across gender, age, region, and country for 1990 and 2021, using age-standardized rates. Trend analysis assessed the average changes in these rates from 1990 to 2021 by calculating the estimated annual percentage change (EAPC). Projections for future burden were made using the exponential smoothing (ES) model and the autoregressive integrated moving average (ARIMA) model.ResultIn 2021, T2DM attributed to low physical activity caused 149,214 deaths and 5,523,050 DALYs, with significant increases since 1990. Both age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life years (DALYs) rate (ASDR) rose, especially among females. The highest burden occurred in the 95+ and 70–74 age groups. High-SDI regions had the highest rates, with rapid increases in the high-middle SDI regions. Countries like the UAE, Montenegro, and Hungary showed the highest rates. Projections from 2022 to 2050 indicate a steady rise in deaths and DALYs, with a peak in 2050, though the rate of increase is slower according to the exponential smoothing model.ConclusionThe burden of T2DM attributable to low physical activity has steadily increased, with concerning future trends.